Surgical Management of Deep-Seated Metastatic Brain Tumors Using Minimally Invasive Approaches - Gassie, Kelly; Alvarado-Estrada, Keila; Bechtle, Perry; Chaichana, Kaisorn L. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background and Study Aims/Objective Metastatic brain tumors are the most common type of adult brain tumors. Treatment involves surgery and/or radiation therapy. Surgery is typically reserved for patients with good neurologic function, solitary and accessible lesions, symptomatic lesions, and/or those with good systemic control of their primary cancer. Deep-seated lesions, however, are typically treated with palliative options including radiation and medical therapies. We summarize our personal experience with minimally invasive surgical approaches for these deep-seated metastatic brain tumors using tubular retractors with exoscopic visualization.Material and Methods Patients with deep-seated metastatic brain tumors who were operated on from January 2016 to December 2017 by the senior author were collected prospectively. “Deep seated” was defined as any subcortical location below the deepest adjacent sulcus in close proximity to the basal ganglia and/or thalamus. “Minimally invasive” was defined as the use of tubular retractors with exoscopic visualization.Results A total of 15 consecutive patients with an average ± standard deviation age of 63 ± 12 years underwent surgical resection of a deep-seated metastasis. The tumor was located in the centrum semiovale in seven (47%) (3 corticospinal tract, 2 superior longitudinal fasciculus, 1 visual tract, 1 inferior frontal occipital fasciculus), basal ganglia in three (20%), thalamus in two (13%), and cerebellum in three (20%). Median percentage resection was 100% (interquartile range:100–100%), and, following surgery, seven (47%), seven (47%), and one (7%) had an improved, stable, and worse Karnofsky Performance Score, respectively. No patients had notable local complications including stroke, infection, hemorrhage, and/or seizure. All patients underwent postoperative stereotactic radiosurgery.Conclusion This minimally invasive approach can be used to achieve extensive resection with minimal morbidity for arguably the highest risk metastatic brain tumors.
Keywords: deep seated; exoscope; metastatic brain tumors; minimally invasive approaches; tubular retractors